A Covalently Imprinted Photonic Crystal for Glucose Sensing. (17th June 2013) - Xue, Fei; Duan, Ting-rui; Huang, Shu-yue; Wang, Qiu-hong; Xue, Min; Meng, Zi-hui
Abstract : We demonstrate a glucose-sensing material based on the combination of photonic crystal templating and a molecular-imprinting technique. In the presence of the target molecule glucose, poly( N -isopropylacrylamide-co-2-hydroxyethyl methacrylate) hydrogel with pendent phenylboronic acid groups was synthesized in the void of a poly(methyl methacrylate) (PMMA) colloidal crystal. After removing the PMMA photonic crystal template and glucose molecules, a 3D-ordered porous covalently imprinted photonic crystal (CIPC) hydrogel was created. The unique 3D-ordered porous hydrogel revealed optical changes in response to glucose concentration. At pH = 11 and 37 ∘ C, the diffraction of CIPC redshifted from 725 nm to 880 nm in response to 20 mmol L −1 glucose. Due to the covalently imprinted recognizer, boronic acid group, the selectivity of the CIPC towards glucose over D -ribose and L -rhamnose was improved significantly.